2010
DOI: 10.1039/b919954c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of carbon nucleophiles with alkylideneindazolium and alkylideneindolium ions generated from their 3-(1-arylsulfonylalkyl) indazole and indole precursors

Abstract: Lewis acid promoted elimination of p-toluenesulfinc acid from sulfonyl indazoles and sulfonyl indoles generates the corresponding iminium ion that reacts with allyltin reagents, silyl enol ethers, silyl ketene acetals and electron-rich aromatics leading to functionalized indazole and indole derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…For preliminary trials, the allylation reaction was attempted on sulfonyl indazole 65 using allyltributyltin as a nucleophile in the presence of different Lewis acids ( Table 2). [63] Surprisingly, TiCl 4 and SnCl 4 , which were the most effective acids with a-amido sulfones, gave poor results in this reaction ( Table 2, entries 1 and 2). The utilization of AlCl 3 showed a more promising result and, by tuning the acidity level through introducing alkyl substituents at the metal center, we finally found that AlEtCl 2 was the best promoter for our process ( Table 2, entries 3 and 4).…”
Section: Reaction With Enol Ethers and Allyl Derivatives Under Acidicmentioning
confidence: 96%
See 1 more Smart Citation
“…For preliminary trials, the allylation reaction was attempted on sulfonyl indazole 65 using allyltributyltin as a nucleophile in the presence of different Lewis acids ( Table 2). [63] Surprisingly, TiCl 4 and SnCl 4 , which were the most effective acids with a-amido sulfones, gave poor results in this reaction ( Table 2, entries 1 and 2). The utilization of AlCl 3 showed a more promising result and, by tuning the acidity level through introducing alkyl substituents at the metal center, we finally found that AlEtCl 2 was the best promoter for our process ( Table 2, entries 3 and 4).…”
Section: Reaction With Enol Ethers and Allyl Derivatives Under Acidicmentioning
confidence: 96%
“…Although the allyl moiety was amenable to further synthetic manipulations at the double bond, we sought a more direct introduction of useful functional groups through the utilization of weak nucleophilic reagents compatible with the employed Lewis acid, such as silyl enol ethers, silyl ketene acetals, and electron‐rich aromatic compounds (Scheme ) 48,63. All of these nucleophiles were effective, leading to valuable functionalized indazole and indole derivatives 69 in satisfactory yields.…”
Section: Reaction With Enolate Systemsmentioning
confidence: 99%
“…Lewis acid promoted elimination of p-toluenesulfonic acid from sulfonyl indazoles and sulfonyl indoles generates the corresponding iminium ion that reacts with allyltin reagent, silyl enol ethers, silyl ketene acetals and electron-rich aromatics leading to the synthesis of indazole derivatives (Scheme-74) [88].…”
Section: Scheme-73mentioning
confidence: 99%
“…[10] Acidic reagents (Lewistype) are also able to remove the arylsulfinic group from 1 leaving an iminium ion 2 b, which can react with weak nucleophiles thus generating the substituted products 3. [11] An iminium ion structurally related to 2 b is supposed to be active in the indium-catalyzed procedure involving reaction of N-alkyl pyrroles.…”
mentioning
confidence: 99%